The Existence of Government Regulation in Liew of Law or Peraturan Pemerintah Pengganti Undang-Undang (Perppu) in Legal Systems of the Republic of Indonesia - Rifandy Ritonga (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The Government Regulation in Liew of Law (Perppu)for the legal system in the republic of Indonesia which reflects the executive power is used to overcome “the forcing crunch”. It (Perppu) is one of legislations which is based onPancasila and Indonesian Constitutions in 1954 (UUD 1945) as all sources of law and the basic law of the country in legislation, and should be able to be a source of law legislation which is lower . But in practice it is often found that there are still some problems related to existence and function of  the Government Regulation in Liew of Law (Perppu). Therefore, it has to arrange amendment to Act no. 10 of 2004 and Act no. 12 of 2011 on the Establishment Regulation Legislation clarifying in finding solutions, especially  the definition of " the forcing crunch " .